Kościół katolicki na Islandii do roku 1264 - Grzegorz Adamiak, (Annales Missiologici Posnanienses, 2019)
The missionary action in Iceland did not end with the reception of Christianity by Althing in the year 1000. Further eﬀ orts of the missionaries and their cooperation with Icelandic society were necessary to consolidate the adopted faith. The missionaries from Germany and England ﬁ rst had a huge share here. Then, the native bishops and clergy took over this role successfully. The political and social stabilization of this period allowed Christianity to take root in the society of the Icelandic time of the independent Icelandic Community. This was conﬁ rmed by the rise and development of monastic life, the development of Icelandic culture and education. The ﬁ rst period of Christianity in Iceland allowed for laying solid foundations on which, even after the loss of sovereignty, Icelanders could preserve their cultural identity and national heritage.